Job Satisfaction of Teachers and Student's Performance in Academics in Public Secondary Schools - Olawale Abayomi Onikoyi (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study is to examine job satisfaction and academic achievement in secondary schools in the Ifako Ijaiye Local Government Area of Lagos State. The study was conducted using a descriptive survey research approach. Using a proportional random selection technique, 246 teachers from eight public secondary schools in the Ifako Ijaiye Local Government Area of Lagos State made up the study's sample size. Teachers’ Job Satisfaction and Academic Performance of Students Questionnaire (TJSAPQ) was the self-structured questionnaire used as the research tool for this study. The four-point Likert scale type was used in its creation. To examine participant biodata, descriptive statistics of percentages were utilized. Percentage and mean were then used to respond to the study questions, and Pearson Product Moment Correlation statistical tools were used to test the hypotheses. The researcher concluded that the academic performance of secondary schools in the Ifako Ijaiye Local Government Area was substantially connected with teachers' satisfaction with pay, promotion, working conditions, and human relations. However, there is no correlation between secondary school academic achievement in Ifako Ijaiye local government area and teachers' contentment with principal supervision. It was suggested that school administration and the education board acknowledge and suitably reward teachers' efforts.